Validation and Factor Analysis of the Child and Youth Resilience Measure for Indigenous Australian Boarding School Students - Langham, Erika; McCalman, Janya; Redman-MacLaren, Michelle; Hunter, Ernest; Wenitong, Mark; Britton, Amelia; Rutherford, Katrina; Saunders, Vicki; Ungar, Michael; Bainbridge, Roxanne (Frontiers in Public Health, 2018)
Introduction: Resilience is a strengths-based construct that is useful for understanding differences in health and wellbeing among youth. There are a range of validated survey instruments available to measure resilience for Aboriginal and Torres Strait Islander (hereafter respectfully Indigenous1) youth. However, standard international instruments should only be used if they have been subjected to a rigorous cross-cultural adaptation process and psychometric evaluation in the target population to ensure their validity. The aim of the study was to validate an adapted Child and Youth Resilience Measure (CYRM-28) within a sample of Indigenous Australian boarding school students. Method: The CYRM-28, augmented with an additional 11 site specific items was administered to a purposive sample of Australian Indigenous boarding school students (n = 233) as part of the broader T4S survey instrument that captures demographic information and measures resilience, psychological distress and risk, and service usage. Confirmatory factor analysis was undertaken to verify the relationship between the observed variables with the theoretical constructs of the CYRM-28 and previous findings on the factor structure. Cronbach alpha was also calculated to assess the internal consistency of the CYRM-28 within this sample. Results: Survey data were not a good fit for any previously identified models of the CYRM-28, although the inclusion of a site-specific variable improved the overall fit statistics. Two separate scales were confirmed that capture the sources and expressions of resilience for Indigenous Australian boarding school students. This structure is different to previous findings in relation to the CYRM-28, but consistent with conceptualizations of resilience as a dynamic process. Conclusions: The findings are useful in guiding the future use of the CYRM-28 instrument, explorations of Indigenous youth resilience, and for services working with Indigenous youth in out of home care situations. They highlight contextual differences in the measurement of resilience and the importance of validating standard instruments that have been subjected to rigorous cross-cultural adaptation processes. The two scales offer practical guidance to human services working with Indigenous youth on strategies to build and monitor resilience in Indigenous Australian youth and contribute to the emergent understanding of their resilience.